Circulating proteomic biomarkers related to the development of chronic thromboembolic pulmonary hypertension in patients with acute pulmonary embolism. (14th October 2021) - Quan, R; Ding, Y; Yang, Y; He, J
Abstract: Background: Chronic thromboembolic pulmonary hypertension (CTEPH), known as a complication of acute pulmonary embolism (PE), can be attributed to both persistent organized thrombi and small-vessel disease. It has been reported that patients with acute PE are more likely to develop CTEPH or have a worse prognosis in follow-up if they have pulmonary hypertension (PH) or right ventricular dysfunction in their acute phase; in acute PE, increased pulmonary arterial pressure can be induced by a combination of mechanical obstruction and pulmonary vasoconstriction. However, it remains unknown whether contributors to the increase pulmonary arterial pressure in acute phase would persistently influence the pulmonary vasculature, which could further lead to the development and progression of CTEPH. Purpose: To investigate underlying contributors related to pulmonary hypertension in acute PE that would persistently influence the pulmonary vasculature in the development of CTEPH, and to explore potential biomarkers predictive of CTEPH in acute PE. Methods: Plasma from patients with acute PE were collected and classified into Group 1 (with PH) and Group 2 (without PH) according to the presence of PH, which was defined by echocardiographic estimated "high probability" of PH as recommended in the 2015 ESC/ERS Guidelines for the diagnosis and treatment of PH. In addition, plasma from patients with acute PE who had not developed PH both in their acute and follow-up phase but had persistent thrombi (Group 3) were also studied and compared to that of CTEPH patients (Group 4). Differential expression proteins (DEPs) between 4 groups were identified in terms of data-independent acquisition-based quantitative proteomic analysis. Results: Twenty-two DEPs were identified between Group1 and Group 2, and 105 DEPs were identified between Group 3 and Group 4. Among two groups of DEPs, 8 proteins were in common: antithrombin-III, osteopontin, properdin, desmoplakin, C1QA (complement C1q subcomponent subunit A), LDHA (L-lactate dehydrogenase A chain), IGKV1D-33 (immunoglobulin kappa variable 1D-33) and PEPD (Xaa-Pro dipeptidase). The level of LDHA, antithrombin-III, osteopontin and properdin were decreased both in acute PE patients with PH and CTEPH patients, while the level of desmoplakin, C1QA and IGKV1D-33 were increased in the above two groups. Regarding PEPD, its level was lower in acute patients with PH but was higher in CTEPH. Based on underlying pathogenic mechanism and the percentage of missing value, osteopontin, properdin, desmoplakin, C1QA, LDHA and PEPD were further validated as potential biomarkers predictive of CTEPH in acute PE. Conclusions: Contributors to the increase pulmonary arterial pressure in acute PE can be further involved in the development of CTEPH, and these proteins can be potential biomarkers to help guide the management and follow-up strategy in acute PE. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Chinese Academy of Medical Sciences Innovation Fund for Medical Sciences (CIFMS; No. 2017-12M-1-009); National Key Research and Development Program of China (No: 2016YFC1304400)